2022
DOI: 10.7717/peerj.14340
|View full text |Cite
|
Sign up to set email alerts
|

Use of fermented spent coffee grounds as a substrate supplement for rearing black soldier fly larvae, Hermetia illucens (L), (Diptera: Stratiomyidae)

Abstract: Background Spent coffee grounds (SCG), an increasingly abundant waste product with environmental disposal problems, has been used as a dietary supplement for many animals and have the potential to be used as a dietary supplement for black soldier fly (BSF) larvae; however, its effective use is still under scrutiny. To date, no studies have considered the use of SCG after microbial fermentation (fSCG) and its effects on BSF life history. Methods A mixture of fruit and vegetable pulp residue supplemented with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…Likewise, the presence of toxic phenolic compounds in SCG could impact the larval growth ( Permana & Ramadhani Eka Putra, 2018 ; Sideris et al, 2021 ). However, fermented SCG, derived from cofermentation with pineapples at levels of less than 60% (w/w) in the substrate mixture gave larger BSFL ( Khaekratoke, Laksanawimol & Thancharoen, 2022 ). Although the SCG used in this study underwent self-fermentation, the BSFL exhibited similar trends.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Likewise, the presence of toxic phenolic compounds in SCG could impact the larval growth ( Permana & Ramadhani Eka Putra, 2018 ; Sideris et al, 2021 ). However, fermented SCG, derived from cofermentation with pineapples at levels of less than 60% (w/w) in the substrate mixture gave larger BSFL ( Khaekratoke, Laksanawimol & Thancharoen, 2022 ). Although the SCG used in this study underwent self-fermentation, the BSFL exhibited similar trends.…”
Section: Discussionmentioning
confidence: 97%
“…The flies were provided with a 30% (w/v) brown sugar solution, which was sprayed onto the mesh chamber three times a day to serve as a food source. Oviposition devices, consisting of a tray filled with an attractant substrate made from a mixture of wheat bran, fruits, and vegetables ( Khaekratoke, Laksanawimol & Thancharoen, 2022 ; Laksanawimol, Singsa & Thancharoen, 2023 ), were placed within the chamber. Wooden sheet pieces were also provided as oviposition substrates placed above the tray of attractant materials.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously mentioned, most of the innovations in the BSF feed are the enrichment of SCG or other coffee parts with algae or their combination with various wastes. However, there is only one research study about the fermented SCG for BSF feed, as reported by Kharkratoke et al [62]. They used fermented SCG in various proportions (0-100%) mixed with fruit and vegetable pulp residue for BSF feed.…”
Section: Cultivation Of Bsf Larvae Using Scg And/or Coffee Partsmentioning
confidence: 99%
“…For example, Nguyen et al ( 16 , 17 ) divided the number of replicates between manipulated and non-manipulated larvae. Khaekratoke et al ( 18 ) increased the number of replicates to reduce the effects of manipulation. Miranda et al, ( 19 ) established a minimum number of larvae sampled.…”
Section: Introductionmentioning
confidence: 99%